2016
DOI: 10.1111/1440-1681.12577
|View full text |Cite
|
Sign up to set email alerts
|

Role of Simvastatin on fracture healing and osteoporosis: a systematic review onin vivoinvestigations

Abstract: SUMMARYSimvastatin is a lipid lowering drug whose beneficial role on bone metabolism was discovered in 1999. Several in vivo studies evaluated its role on osteoporosis and fracture healing, however, controversial results are seen in the literature. For this reason, Simvastatin has not been the focus of any clinical trials as yet. This systematic review clears the mechanisms of action of Simvastatin on bone metabolism and focuses on in vivo investigations that have evaluated its role on osteoporosis and fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 115 publications
0
62
0
Order By: Relevance
“…Indeed, both in vitro and in vivo studies have reported the beneficial effects of statins on osteoblast differentiation and mineralization . Additionally, in vivo studies showed that statins are a potential treatment for osteoporosis . Based on these studies, we expected to find improved MSC‐derived osteoblast differentiation and/or mineralization and we speculated that SIM may antagonize the negative effects of HCQ.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, both in vitro and in vivo studies have reported the beneficial effects of statins on osteoblast differentiation and mineralization . Additionally, in vivo studies showed that statins are a potential treatment for osteoporosis . Based on these studies, we expected to find improved MSC‐derived osteoblast differentiation and/or mineralization and we speculated that SIM may antagonize the negative effects of HCQ.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies have reported the benefits of statins, especially SIM, on bone formation as well as on the inhibition of bone resorption (Horiuchi & Maeda, ; Moshiri, Sharifi, & Oryan, ; Mundy, ; Shah, Werlang, Kasper, & Mikos, ; Zhang et al, ). Within the family of statins, PITA presents some interesting properties, in particular its lower price, hydrophilic properties and its comparable efficiency compared to other statins (i.e., SIM) at much lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…There is one case report of successful teriparatide use in an HIV-infected man with severe osteoporosis [123] although robust data regarding its use in HIV-infected patients are lacking. In addition, the 3-hydroxy-3-methyl-glutaryl coenzyme A (HMG-CoA) reductase inhibitor (statin) simvastatin has been shown to increase osteoblast activity and decrease osteoclastogenesis, and is associated with increased fracture healing in in vivo animal models [124], while pravastatin has been shown to prevent PI-induced senescence in MSCs and restore osteoblastic potential in vitro [89]. Clinically however, in HIV-infected individuals on stable cART who had heightened immune activation, treatment with rosuvastatin for 96 weeks was not associated with any changes in BMD, although it was associated with improvement in lean body mass [125].…”
Section: Management Of Hiv-associated Bone Lossmentioning
confidence: 99%